The Effects of Agricultural Trade Liberalisation under the Doha Development Agenda with Special Reference to the Asia Pacific Region: A Brief Survey - Jayatilleke S. Bandara (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The main purpose of this paper is to survey the results of recent quantitative studies on the effects of Agricultural Trade Liberalization with special reference to the Asia-Pacific region under the July Framework Agreement or the “July Package” of the Doha Development Agenda, DDA (the decision adopted by the General Council of the WTO on 1 August 2004, see WTO, 2004, WT/L/579).
Keywords: F1; 330; Agricultural Trade Liberalization; Doha Development